1993
DOI: 10.2337/diab.42.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypoglycemia and Intelligence in Adult Patients With Insulin-Treated Diabetes

Abstract: The IQ scores (WAIS-R) of 100 patients with insulin-treated diabetes (aged 25-52 yr) were compared with those of 100 healthy control subjects who were matched to the diabetic patients for sex, age, education, and social class. The diabetic group had lower WAIS-R performance and verbal IQ scores than the control group (P = 0.017 and P = 0.033, respectively) after controlling for premorbid IQ. The extent of the difference was modest, representing approximately 33% of an SD in IQ. When frequency of severe hypogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Factors such as exposure to severe hypoglycaemia, depression, macrovascular disease, hypertension, poor metabolic control and microvascular disease may all be implicated. 1,3,8 A few neuropathological studies in humans with diabetes of long duration have reported the presence of structural abnormalities, including microvascular and other changes such as 'pseudocalcinosis'. [9][10][11] However, many of these post-mortem studies were performed on adults who had concurrent renal failure and severe hypertension, which may themselves have been responsible for the neuropathological changes.…”
Section: Introductionmentioning
confidence: 98%
“…Factors such as exposure to severe hypoglycaemia, depression, macrovascular disease, hypertension, poor metabolic control and microvascular disease may all be implicated. 1,3,8 A few neuropathological studies in humans with diabetes of long duration have reported the presence of structural abnormalities, including microvascular and other changes such as 'pseudocalcinosis'. [9][10][11] However, many of these post-mortem studies were performed on adults who had concurrent renal failure and severe hypertension, which may themselves have been responsible for the neuropathological changes.…”
Section: Introductionmentioning
confidence: 98%
“…Several earlier studies have suggested that severe hypoglycemia, over time, is associated with cognitive decline in people with type 1 diabetes [3,4]. When the DCCT reported that recurrent severe hypoglycemia did not permanently impact cognitive function over time [5] (data consistent with those of a smaller study previously published [6]), the report was met with some skepticism [7].…”
mentioning
confidence: 56%
“…(16), a positive correlation between the frequency of severe hypoglycemia and the degree of intellectual deficit was demonstrated. In an extension of the original study, impaired performance IQ was shown to be associated specifically with hypoglycemia, whereas a lower verbal lQwas a feature of diabetes per se and may be related to the social impact of the disease (15). Further characterization of the performance deficit associated with hypoglycemia demonstrated that decision and response initiation processes were affected in preference to the encoding and storage of information (17).…”
Section: Chronic Effects Of Hypoglycemia On Cognitive Functionmentioning
confidence: 96%
“…However, some evidence now suggests that recurrent exposure to severe hypoglycemia may have a deleterious effect on cognitive function which is cumulative and causes a gradual decline in intellectual ability over a period of years (12). Retrospective studies of adult patients with IDDM have demonstrated an association between a history of recurrent severe hypoglycemia (13)(14)(15)(16) and a modest degree of cognitive impairment with a mean lQ deficit of about 6 lQ points (14, 15, 17) (Fig.1). The cognitive deficits included motor skills, problem solving, visuospatial skills and tasks involving frontal lobe function.…”
Section: Chronic Effects Of Hypoglycemia On Cognitive Functionmentioning
confidence: 97%